2007
DOI: 10.1300/j037v16n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Advertising in Czech and French Magazines

Abstract: The aim of this research is to determine the main features in which the Czech and French advertisements are similar and in which they differ. The study concerns the content analysis of 577 printed advertisements published in the 10 most representative magazines in the Czech Republic and France. The five largest categories of magazines in terms of their focus are represented as follows: women, men, businesses, seniors and juniors. The results show some noticeable divergences in the basic structure and content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The observed practices apparently contradict these results, in that the proportion of advertising that uses nudity in Europe does not appear to differ significantly among countries. Koudelova and Whitelock (2001) compare television advertisements in the UK and the Czech Republic, and Dianoux et al (2006) compare advertisements in the Czech Republic and France in five principal categories of magazines (managers, men, women, seniors, teenagers). Both sources indicate differences in some published formats (e.g.…”
Section: Impact Of Nudity Country Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed practices apparently contradict these results, in that the proportion of advertising that uses nudity in Europe does not appear to differ significantly among countries. Koudelova and Whitelock (2001) compare television advertisements in the UK and the Czech Republic, and Dianoux et al (2006) compare advertisements in the Czech Republic and France in five principal categories of magazines (managers, men, women, seniors, teenagers). Both sources indicate differences in some published formats (e.g.…”
Section: Impact Of Nudity Country Variationsmentioning
confidence: 99%
“…The size of the advertisement also may influence attention. In addition, in the Czech Republic, advertisements tend to be published on half-pages rather than full pages (Dianoux et al, 2006). We therefore take this element into account in our experimental design to neutralise any effect due to the more usual custom of Czech advertising in smaller formats.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Among the many different aspects of product advertisements that may determine consumer response, relatively little attention has been paid to the role of language choice (Grin, 1994;Holden 1987), at least compared to the role of other similar variables such as cultural values (Aaker & Maheswaran, 1997;Aaker & Williams, 1998;Dianoux, Kettnerová, & Linhart, 2007;Rustogi, Hensel, & Burgers, 1996) and visual rhetoric (McQuarrie & Mick, 1999;McQuarrie & Mick, 2003).The majority of the studies on the impact of language choice in product ads are concerned with the effect of using language A compared to using language B on consumers who are (near) native speakers of both languages A and B. The respondents used in these studies are representative of consumers in bilingual societies such as the Hispanic community in the United States (Grin, 1994;Koslow, Shamdanasi, & Touchstone, 1994;Luna & Peracchio, 2001, 2005Luna, Ringberg, & Peracchio, 2008;Roslow & Nichols, 1996), the Korean American community in the United States (Dublish, 2001), or the bilingual Hindi-English community in India (Krishna & Ahluwalia, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study also found that contrary to Russia's cultural stance on uncertainty avoidance, Nestlé's chocolate TV commercials used low-uncertainty avoidance appeals such as youth, adventure, casual and magic (Larimo and Pesonen, 2008). Another study comparing print advertising from the Czech Republic and France by Dianoux et al (2007) found considerable divergences in the content and structure of advertising, though both countries are relatively similar on various Hofstede indices.…”
mentioning
confidence: 99%